THE FEAST OF HEROD: A NEW STAGE IN RELIGIOUS NARRATIVE AND SCULPTURE DONATELLO’S VISION OF SCENE, EMOTION, AND COMPOSITION - Umirzakova Nozigul; Khujayorova Sadokat (Bright Mind Publishing, 2025)
This article gives an in-intensity evaluation of Donatello’s bronze relief "The Feast of Herod", created among 1423 and 1427, as a landmark withinside the improvement of Renaissance sculpture. The painting exemplifies Donatello’s mastery of linear perspective, spatial intensity, and emotional realism, marking a thorough departure from Gothic inventive conventions. Centered round a dramatic biblical narrative, the relaxation portrays the instant while Salome needs the beheading of John the Baptist, shooting complicated ethical topics together with guilt, desire, and power. The observe now no longer most effective explores the technical components of the relaxation—together with using shallow and deep carving, architectural elements, and facial expressions—however additionally contextualizes Donatello’s improvements withinside the broader cultural and creative shifts of the Renaissance. Furthermore, the item highlights Donatello’s enduring have an effect on later generations of artists, which includes painters and sculptors, in addition to his oblique legacy in images and cinema. His specific imaginative and prescient and approach converted visible storytelling in European art.
Keywords: The Feast of Herod, Donatello, renaissance sculpture, religious narrative, iconography, emotional expression, composition, continuous narrative, biblical art, humanism, perspective in sculpture, religious symbolism, European art.